(6y+1+2)/2=(7y-3)/3
3(6y+3)=2(7y-3)
18y-14y=-6-9
4y=-15
y=-15/4
2007-01-07 03:47:28
·
answer #1
·
answered by Maths Rocks 4
·
0⤊
2⤋
7y-6y = 1/2+1+3/3
y = 1/2+1+1
y = 1/2+2
y = 5/2 or 2.5
2007-01-08 00:53:13
·
answer #2
·
answered by angel 2
·
0⤊
0⤋
6y + 1/2 + 1 = 7y - 3/3 changes to 6y + 3/2= 7y - 1
*Eliminate fractions > multiply the denominator by everything >
2(6y) + 2(3/2)= 2(7y) - 2(1)
*Cancel "like" terms and combine the remaining terms >
2(6y) + 3= 2(7y) - 2(1)
12y + 3 = 14y - 2
First: combine "y" variables > subtract 14y from both sides (Opposite side means opposite sign) >
12y - 14y + 3 = 14y - 14y - 2
-2y + 3 = - 2
Sec: subtract 3 from both sides >
-2y + 3 - 3 = - 2 - 3
-2y = -5
Third: divide both sides by -2 >
-2y/-2 = -5/-2
y = 5/2
P.S. since 5/2 can't be simplified into lowest terms > it doesn't need to be changed into a decimal :-)
2007-01-07 13:05:07
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
2⤊
0⤋
6y+1/2+1=7y-3/3
6y+(1/2) = 7y-1-1
1/2 = 7y-6y -2
1/2 = y-2
1/2 +2 = y
1/2 + 4/2 = y
y = 5/2 or 2.5
I hope this one helps. :)
2007-01-07 11:52:06
·
answer #4
·
answered by ... 1
·
2⤊
0⤋
1/2 + 3/3 = 7y-6y ( by transpose)
1/2+ 1 = y
1 1/2 =3/2 =y
2007-01-07 12:14:41
·
answer #5
·
answered by khan_imad 1
·
0⤊
3⤋
6y= -1 1/2-3/3+7y
6y-7y= -2/2 +1/2 - 3/3 3/3=1
-1y=-2/2 +1/2 -2/2
-y=-4/2 +1/2
-y=-3/2
y=1 1/2
2007-01-07 12:38:31
·
answer #6
·
answered by Anonymous
·
0⤊
3⤋
Y=5/2 or 2.5
2007-01-07 11:53:41
·
answer #7
·
answered by Faith 2
·
0⤊
1⤋
Y=2.5
2007-01-07 11:48:14
·
answer #8
·
answered by fob4960 2
·
1⤊
2⤋
(6y+1+2)/2=(7y-3)/3
3(6y+3)=2(7y-3)
18y-14y=-6-9
4y=-15
y=-15/4
2007-01-10 04:34:42
·
answer #9
·
answered by Kinu Sharma 2
·
0⤊
0⤋
Y = 2.5
2007-01-07 12:40:44
·
answer #10
·
answered by MANDAR N 1
·
0⤊
2⤋